(untitled) (Hungarian Journal of Industry and Chemistry, 2011)
The paper deals with the presentation of a complete Measurement Automation System (MAS) implemented in an Aluminium Electrolytic Capacitor Development Laboratory at EPCOS Hungary. The main function of the MAS is to facilitate electrolyte and capacitor research and development by automation of the related measurement tasks and to provide a powerful database system background for data retrieval and decision support. The presentation focuses on the architecture of the spark-detection measurement system and introduces a reliable estimation procedure for determining the maximum level of the voltage which can be applied to the capacitor without damage. For the design engineers it is often impossible to determine the exact maximum voltage which will never be exceeded in the application. With the presented spark detection measurement a good estimation of the allowable maximum voltage can be given.